Pengembangan Sistem Informasi Penyewaan Kendaraan pada CV. Bita Jaya Mandiri - Jefri Junifer Pangaribuan; Ade Maulana; Muhammad Thafa Kurniawan; Jusin Jusin; Romindo Romindo (Yayasan Literasi Sains Indonesia, 2022)
Car rental is a four-wheeled vehicle rental business. CV Bita Jaya Mandiri is a company engaged in car rental services, auto service and body repair. In the process, the problems that occur are the loss of customer data because they are still using semi-computerization, notes made for payments still use written notes and promotions that cannot be carried out widely. Based on these problems the author aims to create a system that can simplify the rental process and provide rental information online. The method used for the car rental information system is an object-oriented approach. In the application of this system development stage, the prototype method is used, the tools used to create the system are Use case diagrams, use case scenarios, activity diagrams, class diagrams and sequence diagrams. The data collection techniques were carried out by means of observation and interviews. With this information system is expected to facilitate the process of leasing and data processing at this company.